Training-induced changes in drag-flick technique in female field hockey players - López de Subijana, C.; Gómez, M.; Martin-Casado, L.; Navarro, E. (Biology of Sport, 2012)
The penalty corner is one of the most important goal plays in field hockey. The drag-flick is used less by women than men in a penalty corner. The aim of this study was to describe training-induced changes in the drag-flick technique in female field hockey players. Four female players participated in the study. The VICON optoelectronic system (Oxford Metrics, Oxford, UK) measured the kinematic parameters of the drag-flick with six cameras sampling at 250 Hz, prior to and after training. Fifteen shots were captured for each subject. A Wilcoxon test assessed the differences between pre-training and post-training parameters. Two players received specific training twice a week for 8 weeks; the other two players did not train. The proposed drills improved the position of the stick at the beginning of the shot (p<0.05), the total distance of the shot (p<0.05) and the rotation radius at ball release (p<0.01). It was noted that all players had lost speed of the previous run. Further studies should include a larger sample, in order to provide more information on field hockey performance.